6(z-7)-95+4z=z

Simple and best practice solution for 6(z-7)-95+4z=z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(z-7)-95+4z=z equation:


Simplifying
6(z + -7) + -95 + 4z = z

Reorder the terms:
6(-7 + z) + -95 + 4z = z
(-7 * 6 + z * 6) + -95 + 4z = z
(-42 + 6z) + -95 + 4z = z

Reorder the terms:
-42 + -95 + 6z + 4z = z

Combine like terms: -42 + -95 = -137
-137 + 6z + 4z = z

Combine like terms: 6z + 4z = 10z
-137 + 10z = z

Solving
-137 + 10z = z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-1z' to each side of the equation.
-137 + 10z + -1z = z + -1z

Combine like terms: 10z + -1z = 9z
-137 + 9z = z + -1z

Combine like terms: z + -1z = 0
-137 + 9z = 0

Add '137' to each side of the equation.
-137 + 137 + 9z = 0 + 137

Combine like terms: -137 + 137 = 0
0 + 9z = 0 + 137
9z = 0 + 137

Combine like terms: 0 + 137 = 137
9z = 137

Divide each side by '9'.
z = 15.22222222

Simplifying
z = 15.22222222

See similar equations:

| 2(6-4x)+3x=-6(x-5) | | 6v-6v=1 | | -32-31= | | 2x+3=-(x+3) | | 20=8*5 | | .27=log(x) | | ax+b=4 | | a^8b^6-a^5b^4+a^4b^9-a^4b^4= | | 5x^4-180x^2+1296=0 | | (2/7)2n | | 2/9n=10 | | x=24t+16 | | 6-5n=4 | | -x=1-15 | | -3c-11=-5+c | | 6(z-7)-(5+4z)=z | | .5(8+6)-2=4+x-2 | | -5.9=y+.31 | | .5(8+6)-2= | | r-8.1=0.4 | | 10q-4p+3r*3-4q+4p= | | 253=x-84 | | ln(y-9)-ln(7)=x+ln(x) | | 216/5= | | -16=5+3v | | P=s-x/2 | | 216/5 | | a/5-2=3 | | 105=5+3-x | | 7x-9=8x-11 | | -2x^2+6x=4.5 | | -3(h+5)+2=4(h+6)+9 |

Equations solver categories